Effects of Walking Training with Restricted Blood Flow on HR and HRV Kinetics and HRV Recovery - Junior, Adalberto Ferreira; Schamne, Julio Cezar; Perandini, Luiz Augusto Buoro; Chimin, Patricia; Okuno, Nilo Massaru (International Journal of Sports Medicine, 2019)
The aim of this study was to investigate the effects of walking training with and without blood flow restriction (BFR) on heart rate (HR) and heart rate variability (HRV) kinetics and HRV recovery. Twenty-one men (53.5±3.2 years; 82.4±13.5 kg; 168.5±7.2 cm) were randomly assigned to two training groups: walk training group with (BFR-W; n=11) and without (NOR-W; n=10) BFR. Before and after training, all subjects underwent body composition evaluation, incremental test, and one constant load test. Walking training was performed 3 times/week, during 6 weeks. Each session was composed by 5 sets of 3-min walking and 1-min rest between the sets. All parameters of HR on- and off-kinetics and RMSSD15 0 parameter of HRV on-kinetics were improved for BFR-W group after training (p<0.05), with an interaction effect for HR on-kinetics parameters and RMSSD15 0 parameter (p<0.05). Also, parameters of time and frequency domain of HRV recovery were also improved in BFR-W after training (p<0.05), with no interaction effect (p>0.05). Additionally, in BFR-W group, RMSSD60s values were improved in some moments after training (p<0.05). Therefore, this study demonstrates that a 6-week walking training with BFR improved cardiac autonomic responses on the onset and recovery of exercise.
Keywords: vascular occlusion; heart rate; heart rate variability; aerobic exercise